Sosialisasi dan Pendampingan Para Pedagang dalam Pemasangan Qris Guna Mendukung Perekonomian yang Kuat di Kelurahan Danukusuman Surakarta - Sulistyowati; Maulana Al Bana Pamungkas (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2022)
This community service aims to provide insight into knowledge to the community, especially merchants in Danukusuman Surakarta Village regarding the Quick Response Code Indonesian Standard or commonly abbreviated as QRIS, namely the unification of various kinds of QR from various Payment System Service Providers (PJSP) using a QR code. Providing insight into the importance of increasing the role of encouraging a strong economy for traders, especially in Danukusuman Surakarta Village.The target of devotion is traders in Danukusuman Surakarta Village. The problem is solved by three stages of activity, namely preparation, implementation and evaluation. Preparation is carried out with a preliminary survey to see conditions in the field regarding merchants' knowledge of QRIS transactions. The implementation was carried out by socialization and assistance using presentation techniques to the public explaining QRIS transactions to merchants in order to support a strong economy in Danukusuman Surakarta Village. Evaluation is carried out activities carried out for each stage by collecting and inferring data from each stage. The results of the socialization and merchant assistance activities showed a success rate with an indication of the suitability of the material and the needs of traders in Danukusuman Surakarta Village, there was a positive response from traders and most of them understood the concept of qris use transactions. Traders have understood the importance of improving the progress of transactions in order to improve the economy in society.